Discovery and characterization of HERV-K (HML-2) integrations in humans and gorillas - Williams, Zachary. (2017)
Abstract: The HERV-K (HML-2) endogenous retrovirus (ERV) clade is the most recently active ERV group in humans, and the only group with human-specific integrations, some of which are insertionally polymorphic. A subset of HML-2 proviruses has some or all ORFs intact, with detectable signals of purifying selection, and expression of these proviruses has been associated with cancer and other diseases. Though no naturally occurring infectious HML-2 provirus is known, these observations raise the possibility that undescribed HML-2 proviruses are still replication competent. If they have been recently active, we predict that rare, intact HML-2 integrations would be detected in surveys of large numbers of human genomes. We anticipated that mining whole genome sequence data from genetically diverse individuals should reveal rare proviral insertions not present in the reference genome. We searched for conserved HML-2 sequences in both unaligned and discordantly aligned reads from the 1000 Genomes Project and the Human Genome Diversity Project, identifying a total of 36 HML-2 non-reference HML-2 proviruses, including 19 previously unreported loci, with insertion frequencies ranging from <0.0005 to >0.75. 4 inserts are present as partial or full length 2-LTR proviruses, one of which has intact ORFs for gag, pro, pol, and env -just the second such provirus identified in humans, after HERV-K113, though, like K113, it is not infectious. Though we did not find an infectious HML-2 provirus in humans, we hypothesized that HML-2 may have maintained infectious activity in other primates. To investigate this possibility, we adapted the tools developed in our first study to search for HML-2 insertions in gorilla whole genome sequence data from the Great Ape Genome Project. We mined sequence data from 21 individual gorillas, and identified 126 putative gorilla-specific insertions. We confirmed 27 of these by PCR and sequencing, including 6 2-LTR proviruses. We also identified an additional 10 2-LTR proviruses and 92 solo LTRs in the most recent gorilla genome assembly, for a total of 129 confirmed gorilla-specific insertions. 7 proviruses have maintained at least one intact ORF, and one provirus at 9p13.3 has intact ORFs for all viral proteins. Phylogenetic and molecular clock analyses suggest that these elements were active much more recently in gorillas than in humans, and it is possible that HML-2 is still circulating in gorillas as an exogenous virus.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Molecular Microbiology.; Advisors: John Coffin, and Naomi Rosenberg.; Committee: Michael Malamy, and Katya Heldwein.; Keywords: Virology, Evolution & development, and Genetics.